The changes of cohesion between students’ social skills as the indicator of social competence and socio-demographic factors - Lekavičienė, Rosita; Antinienė, Dalia (Psichologija, 2012)
One of the main indicators of social competence of personality is social skills. Because the level of development of social skills is related to many internal and external factors, micro and macro environment, it’s very important to find out their intercorrelations, to evaluate the tendencies of changes from a time perspective. The aim of performed survey was to find out how the cohesion of social skills of students and socio-demographic factors changed in the last decade. The first survey was performed in 1998–1999, 623 students from four higher education establishments participated in it. The second survey was performed in 2010–2011, 590 students from seven universities participated in it. In the surveys Ullrich and de Muynck social competence assessment questionnaire (Ullrich and de Muynck, 1998, adapted by Lekavičienė, 1999), which analyses the behaviour according seven factors – (F1) General self-confidence, (F2) Resistance to failures and criticism, (F3) Ability of expressing feelings, (F4) Ability of asking for a favour, (F5) Unyielding, (F6) Ability of demanding, (F7) Feeling not guilty, was used. The internal consistency of factors is sufficient (Cronbach’s alpha varied from 0,60 to 0,80 in both surveys). Statistically significant cohesions were gained (p < 0,05): the importance of gender lessened for two factors of social competence – general self-confidence and feeling not guilty, but the gender is still very important factor to the ability of expressing feelings. The factor of a full family, differently than ten years ago, isn’t important to social competence of students, but in the second survey financial power of family became important and was related to one of the factors of social competence – general self-confidence. The greatest count of cohesions and changes during the last decade between the place of residence (city, town or a village) of students and various factors of social competence were revealed. Two new cohesions between living area, general self-confidence and the ability of demanding were found: even a half of students from villages received low ratings of the scale of self-confidence, when the students from cities dominated between those who are able to demand. Two in the first survey revealed cohesions of ability of expressing feelings and feeling not guilty didn’t change during the last decade. The factor of age in contrast to the first survey is related significantly to the general self-confidence.
Keywords: social skills; social competence; social factors; social and demographic factors